Susceptibility of five strains of vine mealybugs, Planococcus ficus (Signoret), to chlorpyrifos - De Wet, Owen (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2004.